Uji Daya Hambat Beberapa Ekstrak Bahan Alami Terhadap Pertumbuhan Cendawan Pyricularia grisea - Zuraidah Zuraidah; Sri Wahyuni (Biotik, 2018)
Pyricularia grisea is a pathogenic fungus which causing rice blast disease that affected leaf, stems and rice panicles of rice plant. A possible option to reduce the use of synthetic chemical fungicide in managing the blast disease is by using plant natural active ingredients to inhibit the mycelial growth of Pyricularia grisea. This research evaluated the potential uses of bay leaf, tropical almond leaf, and kaffir lime leaf extract in inhibiting pathogenic fungus Pyricularia grisea. A Completely Randomized Design (CRD) with 3 replications and 4 treatments were used in this research.  Work procedures included leaf extracts preparation, pathogenic fungi rejuvenation, growth media preparation and isolates plantation on PDA media. The parameter in this study was the diameter of the Pyricularia grisea inhibition zone. Data was analysed by analysis of variance (ANOVA) at 95% confidence interval with Duncan Multiple Range Test (DMRT) at 5% level (α = 0.05) as post hoc test if significant differences between treatments were detected using SPSS 16.0. The results of this study indicated that the highest concentration (100%) of each plant leaf extract was able to inhibit the mycelial growth of the pathogenic fungus Pyricularia grisea. The zone of inhibition of bay leaf extract was 1.77 mm, tropical almond leaf extract was 2.33 mm and lime leaf extract was 1.52 mm. The largest diameter of the inhibition zone was found on media with tropical almond leaf extract.